2019
DOI: 10.1111/febs.14845
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing lysine acetylation of Escherichia coli type II citrate synthase

Abstract: The citrate synthase (CS) catalyzes the first reaction of the tricarboxylic acid cycle, playing an important role in central metabolism. The acetylation of lysine residues in the Escherichia coli Type II CS has been identified at multiple sites by proteomic studies, but their effects remain unknown. In this study, we applied the genetic code expansion strategy to generate 10 site‐specifically acetylated CS variants which have been identified in nature. Enzyme assays and kinetic analyses showed that lysine acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…Although it has been proposed that bud dormancy release is associated with the cellular metabolism (Beauvieux et al, 2018), there is no evidence showing how the cellular metabolism changes exactly during dormancy release. Previous studies in other species have shown an extensive role of Kac in regulation of cellular metabolism (Venkat et al, 2019; Zhang, Qu, et al, 2017; Zhang, Zhang, et al, 2017; Zhao et al, 2010). For example, in human cells, enoyl‐CoA hydratase‐1 (ECHS1; EC 4.2.1.17) plays a key role in fatty acid metabolism, acetylation of ECHS1 decreases its activity (Zhang, Qu, et al, 2017; Zhang, Zhang, et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although it has been proposed that bud dormancy release is associated with the cellular metabolism (Beauvieux et al, 2018), there is no evidence showing how the cellular metabolism changes exactly during dormancy release. Previous studies in other species have shown an extensive role of Kac in regulation of cellular metabolism (Venkat et al, 2019; Zhang, Qu, et al, 2017; Zhang, Zhang, et al, 2017; Zhao et al, 2010). For example, in human cells, enoyl‐CoA hydratase‐1 (ECHS1; EC 4.2.1.17) plays a key role in fatty acid metabolism, acetylation of ECHS1 decreases its activity (Zhang, Qu, et al, 2017; Zhang, Zhang, et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Malate dehydrogenase (MDH, EC 1.1.1.37) catalyzes the NAD/NADH‐dependent inter‐conversion of the substrates malate and oxaloacetate in the TCA cycle, and acetylation of MDH activates its activity (Zhao et al, 2010). Citrate synthase (CS, EC 2.3.3.1) catalyzes the first reaction of the TCA cylce, and Kac of CS could decrease the overall CS activity in Escherichia coli (Venkat et al, 2019). In our study, we checked the effect of Kac modifications on PDH and IDH, another two key enzymes involved in pyruvate metabolism and the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CheY is an essential regulator of chemotaxis, the mechanism through which bacteria respond to changes in the chemical compositions of their environment. In addition to CheY, the N-hydroxyarylamine O-acetyltransferase (NhoA) protein, the citrate synthase (Cs) and the isocitrate dehydrogenase (IcdH) enzymes, both of them belonging to the tricarboxylic acids cycle, and the adenosylmethionine synthase (MetK) are also substrates of CobB sirtuin (Zhang et al, 2013;Sun et al, 2016a;Venkat et al, 2018Venkat et al, , 2019. Recently, the activity and stability of E. coli diguanylate cyclase DgcZ has also been demonstrated to be regulated by deacetylation catalyzed by CobB sirtuin (Xu et al, 2019).…”
Section: Sirtuins In Carbon and Nitrogen Metabolismmentioning
confidence: 99%
“…The LC-MS/MS analyses were performed by Yale University Keck Proteomics Facility following previous protocols (Venkat et al, 2019). The purified ThrRS was digested in gel by trypsin and analyzed by LC-MS/MS on an LTQ Orbitrap XL equipped with a nanoACQUITY UPLC system.…”
Section: Mass and CD Spectrometrymentioning
confidence: 99%